Resilience influence, goals and social context in the academic achievement of high school students - José Concepción Gaxiola Romero; Sandybell González Lugo; Zita Guadalupe Contreras Hernández (Universidad Autónoma de Baja California, 2012)
The academic achievement in high school students of Mexico, according to national and international evaluations has been insufficient. In spite of this situation, is possible to find excellent students, even in the context of sharing negative contextual and physical conditions. There are few investigations that describe the variables associated to resilient students. The alumni that are beyond the risks are called resilient (Rutter, 2007). The aim of this research was to explore and identify the internal variables: goals and resilience, and the external variables: risky neighborhood and risky friends that predicted the scholar achievement of high school students. To measure those variables, was used a compilation of scales validated in the region. The data were analyzed using structural equation modeling, and show that resilience predicted indirectly the scholar achievement trough the academic goals. The results could be used in programs to improve the academic achievement of this group of students.